PENDIDIKAN KARAKTER MELALUI PROGRAM SANTRI DI PONDOK PESANTREN AMANATUL UMMAH MOJOKERTO - Shobichatul Muniroh; Hasyim Asy'ari (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
This research is based on the fact that when students enter adolescence, drastic physical and psychological changes usually occur. So that immoral acts continue to occur, various lifestyles that are far from the nuances of God and juvenile delinquency. This is due to the lack of role models and weak moral control. In order for changes to remain under control, there needs to be good, consistent and continuous guidance and coaching carried out in Islamic boarding schools. This research uses a case study approach with a qualitative research type. The data collection techniques used were interviews, observation and documentation. The results of this research show that the Islamic boarding school activity program leads to a program of religious activities carried out by the students, including: getting used to night prayers, getting used to congregational prayers, routine reciting books and routine reading Aurod. The santri activity program aims to form a non-religious character, including: the character of discipline is carried out by encouraging and absenting the presence of the santri, the character of responsibility is implemented by the santri being responsible for leading activities, the character of hard work is formed through continuous invitations and reminders to take part in santri program activities, the social caring character is implemented through the students' concern for their fellow students by helping and reminding each other through interactions with the students' program activities.